Knowledge and Awareness about Barodontolgia among Undergraduate Dental Students - Snigdha, Dr. M. V. N.; Prathap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Kumar, Dr. V. Srujan; Singh, Surbhit (International Journal Of Drug Research And Dental Science, 2025)
Introduction: Dental pain caused by barometric pressure is a clinical condition provoked by pressure changes in the atmosphere. Barodontalgia (or aerodontalgia) in pilots is of significant concern since it can be a flight safety risk and impair the personnel’s operational ability and performance. Because of its similar signs and symptoms, it can also go unnoticed and manifest itself during a pressure change which can be during flight ascend or descend. Objective: To evaluate the presence of barodontalgia and knowledge of the phenomenon among Indian-based commercial pilots. Materials and Methods: A cross-sectional study was carried out between June and August 2020 through a self-reported questionnaire submitted through Google Forms (Alphabet, Mountain View, CA, USA) among 410 Indian-based pilots. It included questions asking. Regarding the incidence, localisation, severity, and frequency of in-flight dental pain. Inferential statistics were carried out using Chi-square test, One way analysis of variance (ANOVA), and Independent t-test. The statistical significance level was 0.05. Results: 370 pilots filled out the questionnaire with a response rate of 90.24%. Incidence was seen in 10.54% (n=39) pilots despite 42.7% (n=158) being unaware of the same. Recurrence of pain was reported in only one case while none reported any threat to flight safety or accident, secondary to barodontalgia. Conclusion: The level of incidence of barodontalgia in commercial pilots in India is low. Still, the unawareness remains a disquieting risk and was not found to be of any difference when compared on the grounds of gender and work experience.